2015
DOI: 10.1002/pad.1717
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Information and Communication Technology in Public Administration

Abstract: Summary Over the last decades, governments all over the world have tried to take advantage of information and communication technology (ICT) to improve government operations and communication with citizens. Adoption of e‐government has increased in most countries, but at the same time, the rate of successful adoption and operation varies from country to country. This article outlines the evolution of ICT in the public sector over the past 25 years. It presents general trends by examining interactions and mutua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 47 publications
(52 reference statements)
0
43
0
8
Order By: Relevance
“…The data was gathered in a time frame from January to April 2016 and encompasses the time period from 2000 until 2016. This period was selected because [31] found that research on the use of ICT by public entities only slowly started to be of academic interest before the millennium change. This evidence is supported by the fact that the EGRL contains only 84 references before the year 2000.…”
Section: Collection and Pre-processing Of Journal Articlesmentioning
confidence: 99%
“…The data was gathered in a time frame from January to April 2016 and encompasses the time period from 2000 until 2016. This period was selected because [31] found that research on the use of ICT by public entities only slowly started to be of academic interest before the millennium change. This evidence is supported by the fact that the EGRL contains only 84 references before the year 2000.…”
Section: Collection and Pre-processing Of Journal Articlesmentioning
confidence: 99%
“…Regarding another fashionable topic, information and communication technology (ICT), Liu and Yuan () argue that despite massive strides globally, new management approaches, governance structures and policy frameworks are still missing. For developing countries to successfully adopt ICT, systematic analyses need to be conducted to understand how interactions among stakeholders and ICTs are interrelated and co‐create the information environment for good public administration and governance.…”
Section: Reflections On Public Administration and Management For Devementioning
confidence: 99%
“…The change in the operational environment is taking place in both the private and public sectors. In this paper, we focus on the public sector, where municipalities, cities, agencies, and other public sector organizations have started to utilize different IT solutions to improve their customer service, cut costs, and gain greater efficiency [29]. So-called smart city endeavors are becoming common [11].…”
Section: Introductionmentioning
confidence: 99%